Understanding portfolio management service of IDLC Investments Limited with a view to discover an undergraduate finance major’s to-do list - a BRACU perspective - Hasan, S M Muyeed (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.